2020
DOI: 10.1038/s41598-020-57858-2
|View full text |Cite
|
Sign up to set email alerts
|

A screening-level assessment of the pollinator-attractiveness of ornamental nursery stock using a honey bee foraging assay

Abstract: In urban and suburban landscapes characterized by extensive designed greenspaces, the support of pollinator communities hinges significantly on floral resources provided by ornamental plants. The attractiveness of ornamental plants to pollinators, however, cannot be presumed, and some studies suggest that a majority of ornamental plant varieties receive little or no pollinator visitation. Here, we harness the sampling power of the western honey bee, a generalist pollinator whose diet breadth overlaps substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
0
14
1
Order By: Relevance
“…More research on the attractiveness of native and non-native ornamental plants (e.g. Sponsler et al, 2020) to specialist and generalist species in nurseries may shed light on such patterns.…”
Section: Discussionmentioning
confidence: 99%
“…More research on the attractiveness of native and non-native ornamental plants (e.g. Sponsler et al, 2020) to specialist and generalist species in nurseries may shed light on such patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The plants detected using DNA metabarcoding and melissopalynology have been compared in previous studies with concordance found between the two methods 45 – 48 . Both methods detect the same major taxa, but rarer species in a sample are less likely to be found consistently, both when comparing methods and also during replicates of the same method 45 – 47 .…”
Section: Methodsmentioning
confidence: 92%
“…Ornamental plant nurseries represent a major agricultural sector that remains relatively unexplored with regard to its support of local insect communities. While ornamental plants and the urban greenspaces they occupy are well known to serve as foraging resources for pollinators [1,2], the role of horticultural nurseries as bee foraging habitat has just recently received attention [3][4][5][6]. While these facilities occupy less land area than conventional row crops do [7], their high floral diversity [3][4][5] and the potential for exposure to elevated concentrations of insecticides in floral resources [8][9][10] render nurseries pertinent to study from the perspective of wild bee ecology.…”
Section: Introductionmentioning
confidence: 99%
“…While ornamental plants and the urban greenspaces they occupy are well known to serve as foraging resources for pollinators [1,2], the role of horticultural nurseries as bee foraging habitat has just recently received attention [3][4][5][6]. While these facilities occupy less land area than conventional row crops do [7], their high floral diversity [3][4][5] and the potential for exposure to elevated concentrations of insecticides in floral resources [8][9][10] render nurseries pertinent to study from the perspective of wild bee ecology. However, we lack quantitative knowledge on how local management practices in horticulture may interact to affect resident wild bees, particularly solitary species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation